ANALISIS PENANGGALAN DALAM TRADISI REKENG-REKENG DI KELURAHAN GANTARANG KECAMATAN TINGGMONCONG KABUPATEN GOWA PERSFEKTIF ILMU FALAK - Ashari Yusran; Irfan; Sohra (HISABUNA: Jurnal Ilmu Falak, 2023)
This study discusses the Calendar System in the Rekeng-Rekeng Tradition in Gantarang Village, Tinggimoncong District, Gowa Regency, from the Perspective of Astrology. The opinion of the people in Gantarang Village on the calendar system in the rekeng-rekeng tradition has been embedded in people's lives because it has long been used and has become a hereditary tradition by looking at the position of the rising moon to see a good time to do an activity. Some people in carrying out the rereng-rengk tradition use script guidelines and also ask people who are experts in rereng-rengk. The calendar system in the tradition of receng-reng in the perspective of Falak Science uses the lunar circulation system or the Hijri calendar. It's just that the calendar in this rereng-rekeng tradition is special. The rereng-rengk tradition has a function as a habit of looking for a good day to start activities. In determining good days and bad days, it is based on the events that have happened to the people of Makassar, especially in Gantarang Village, they believe that natural processes, in this case the change of the moon, have a mythological meaning which will then affect all human activities, even being trusted and used as a guide in starting activities.